Virtual identities and digital culture - Kannen, Victoria, 1981-; Langille, Aaron (Abingdon ; New York, NY : Routledge, 2023)
"This collection investigates how our online identities and cultures are embedded within the digital practices of our lives, exploring how we form community, how we play, and how we re-imagine traditional media in a digital world. The collection explores a wide range of digital topics - from dating apps, microcelebrity, and hackers to auditory experiences, Netflix algorithms, and live theatre online - and builds on existing work in digital culture and identity by bringing new voices, contemporary examples, and highlighting platforms that are emerging in the field. The book speaks to the modern reality of how our digital lives have been forever altered by our transnational experiences - one of those key experiences is the pandemic, but so too is systemic inequality, questions of digital privacy, and the role of joy in our online lives. A vital contribution at a time of significant social and cultural flux, this book will be highly relevant to those studying digital culture within media, communication, cultural studies, digital humanities, and sociology departments"--
Keywords: Self-presentation.; Online identities; Identity (Psychology); Digital media; SOCIAL SCIENCE / Media Studies